ASPECTS OF SUGAR CANE PRODUCTION IN RURAL PROPERTIES FROM THE MUNICIPAL OF MORRETES, PR - TRENTO FILHO, Airton José; DAROS, Edelclaiton; MACCARI JÚNIOR, Agenor; FERNANDES, José Sebastião da Cunha; ZAMBON, José Luis Camargo (Scientia Agraria, 2008)
This work had as objective to identify the profile of the sugar-cane production in the municipal district of Morretes through the collection of data in ten properties sampled. In Morretes the main purpose of the sugar-cane is the production of the fire-water, being like this, a questionnaire was applied to the producers through interviews during the months of November and December of 2006 to identify the producers and the techniques used in the cultivation of the cane, as well as the aptitude of each producer, characterizing like this the profile of the sugar-cane production. Among the appraised producers were observed that there is the prevalence of small areas with the cultivation of the sugar-cane due to the difficulty of control of the harmful plants and maintenance of the sugar-cane with the crop and fertilization. The fertilization is accomplished mainly through the use of input of vegetable source or animal manure, not using chemical fertilizers. With relationship to the labor an absence of the children of producers exists acting as enterprising and innovative in the cultivation activity and processing of the sugar-cane in the municipal district.